Transverse optical phenomena with Gaussian beams and optical vortices - AMARAL, Anderson Monteiro (2016)
In this thesis are presented various results regarding the transverse structure of light beams in the paraxial propagation regime, with a special concern with singularities in the transverse profile and in nonlinear optics applications. Theoretical and experimental tools were developed for the study of Optical Vortices (OV) and its most important characteristics, as the Orbital Angular Momentum (OAM) and the Topological Charge (TC). In a first step, we theoretically described and experimentally demonstrated that it is possible to shape the intensity profile of a beam containing OV by distributing TC over the plane transverse to the propagation direction [1]. The TC is associated with a phase singularity that implies in points of zero intensity. By distributing the TC on the transverse plane, it is possible to shape the beam dark region and also the OAM profile with the goal of optimizing the light beam for a given application. However, a problem identified in [1] was that most of the current available techniques to characterize OAM light implicitly assume that the beam has cylindrical symmetry, thus being inadequate to characterize fields resulting from more general TC distributions. These problems were approached in a second work [2], where it was shown that by measuring the field transverse amplitude and phase profiles it is possible to measure the OAM and the TC in TC distributions with arbitrary geometries. By combination of the results [1] and [2] it is possible to optimize and characterize the TC distributions for given applications, as for example by designing the transverse forces in an optical tweezer for microparticle manipulation. An important theoretical unfold during these works was the identification of an analogous relation between the field transverse phase in a TC distribution with the Coulomb potential in two-dimensional electrostatics. We then introduced in [3] the Topological Potential (TP) concept which allows the design of structured optical beams with complex spatial profiles inspired by two-dimensional electrostatics analogies. The TP can be used to describe a broad class of TC distributions, as those from [1,2] or the more sophisticate examples in [3]. In another set of results, it is discussed the possibility of using concepts and the formalism of quantum mechanics to solve light propagation problems in the classical approximation. Among the results obtained, it should be remarked that the formalism obtained has a simple and direct relation with ABCD matrices and ray optics [4]. These results were used to understand light propagation in systems containing nonlinear materials, as in SLIM [5] and D4σ [6] techniques. In [5, 6] the theoretical results were compared with experimental data obtained from standard samples, as carbon dissulfide (CS2), acetone and fused silica. It was obtained a very good agreement between the measured optical nonlinearities and the results established in literature for these materials.